Salicylic Acid-Responsive Factor TcWRKY33 Positively Regulates Taxol Biosynthesis in Taxus chinensis in Direct and Indirect Ways - Chen, Ying; Zhang, Hua; Zhang, Meng; Zhang, Wenli; Ou, Ziqi; Peng, Zehang; Fu, Chunhua; Zhao, Chunfang; Yu, Longjiang (Frontiers in Plant Science, 2021)
Taxol is a rare secondary metabolite that accumulates considerably in Taxus species under salicylic acid and methyl jasmonate treatment. However, the molecular mechanism of its accumulation remains unclear. We investigated TcWRKY33, a nuclear-localized group I WRKY transcription factor, as an SA-responsive regulator of taxol biosynthesis. Overexpression and RNA interference of TcWRKY33 confirmed that TcWRKY33 regulates the expression of most taxol biosynthesis genes, especially 10-deacetylbaccatin III-10-O-acetyltransferase (DBAT) and taxadiene synthase (TASY), which were considered as key enzymes in taxol biosynthesis. Transient overexpression of TcWRKY33 in Taxus chinensis leaves resulted in increased taxol and 10-deacetylbaccatin (10-DAB) accumulation by 1.20 and 2.16 times compared with the control, respectively. Furthermore, TcWRKY33, DBAT and TASY were confirmed to respond positively to SA signals. These results suggested that TcWRKY33 was the missing component of taxol biosynthesis that responds to SA. Sequence analysis identified two W-box motifs in the promoter of DBAT but not in the TASY. Yeast one-hybrid and dual-luciferase activity assays confirmed that TcWRKY33 can bind to the two W-boxes in the promoter of DBAT, upregulating its expression level. Hence, DBAT is a direct target of TcWRKY33. Furthermore, TcERF15, encoding a TASY activator, also contains two W-boxes in its promoter. Yeast one-hybrid and dual-luciferase activity assays further confirmed that TcWRKY33 can upregulate TASY expression through activation of TcERF15. In summary, TcWRKY33 transmits SA signals and positively regulates taxol biosynthesis genes in two ways: directly and through the activation of other activators. Therefore, TcWRKY33 is an excellent candidate for genetically engineering regulation of taxol biosynthesis in Taxus plants.